Comparación in vitro del sellado apical entre dos sistemas de obturación termoplastificada: Guttacore y E&Q Master - Hidalgo Moya, Viviana Marcela (2018)
Objective: Compare in vitro the apical seal of thermoplastic filling systems, GuttaCore® and E&Q Master®, from the perspective of microfiltration. Methods: Forty single-rooted teeth were instrumented with rotary system and irrigated with 2.5% sodium hypochlorite and 17% EDTA. The samples were divided into two groups (20 for each system); sealed and placed in the incubator at 37°C and 100% humidity for 3 days. Each sample was covered with colored varnish except the last 3 apical millimiters to be immersed in 2% methylene blue for 3 days and centrifuged for 20 min at 3000 rpm. The samples were washed and fractured axially for their analysis in the stereomicroscope by means of photographs. For the data analysis we used the t Student test with a level of significance of 5%. Results: The mean microfiltration values were 0.660 mm and 0.825 mm for GuttaCore and E&Q Master respectively, no statistically significant differences were found between them (p=0.525). Conclusion: GuttaCore and E&Q Master are seal systems that offer good apical sealing, there is no difference between them.